Multiple-Term Refinements of Young Type Inequalities. (16th November 2016) - Choi, Daeshik
Abstract : Recently, a multiple-term refinement of Young's inequality has been proved. In this paper, we show its reverse refinement. Moreover, we will present multiple-term refinements of Young's inequality involving Kantorovich constants. Finally, we will apply scalar inequalities to operators.